Chiral discrimination of amlodipine from pharmaceutical products using capillary electrophoresis - Melania Cârcu-Dobrin; Alexandra Georgiana Sabău; Gabriel Hancu; Gyéresi Árpád; Aura Rusu; Hajnal Kelemen; Lajos Attila Papp; Anca Cârje (Universidade de São Paulo, 2020)
The present work describes the development of a capillary electrophoresis (CE) method for the chiral discrimination of amlodipine (AML) enantiomers using cyclodextrine (CD) derivatives as chiral selectors. A large number of native and derivatized, neutral and ionized CD derivatives were screened to find the optimal chiral selector; and carboximethyl-β-CD (CM-β-CD) was selected for the enantiomeric discrimination. A factorial analysis study was performed by orthogonal experimental design in which several factors were varied at the same time to optimize the separation method. The optimized method (25 mM phosphate buffer, pH = 9.0, 15 mM CM-β-CD, 15 ºC, + 25 kV, 30 mbar/1 second, detection wavelength 230 nm) was successfully applied for the baseline separation of AML enantiomers within 5 minutes. Successful validation and application of the proposed CE method suggest its routine use in enantioselective control of AML in pharmaceutical preparations.